(untitled) (Altre Modernità, 2012)
Based on the issue of colonial agency and aiming at a revision of Homi Bhabha’s notion of third space, this essay considers two novels roughly based on a dystopian pattern and actually showing two similar interpretations of the Other. The first one, Vonnegut’s Cat’s Cradle (1963), was written as a political and fictional response to the US bombing of Hiroshima and is set in the Republic of San Lorenzo, a Carribbean island whose history has developed through the struggle between a naïf and ruthless dictator, ‘Papa’ Monzano, and a religious leader, Bokonon, who’s made an outlaw though the religion he predicates is professed by almost everyone. The second, Will Self’s The Butt (2008), develops the story of a tourist, Tom Brodzinki, in a tropical island conceived as something of a cross between Australia and Iraq. In both cases, the main focus is the relationship between the Westerner – ex-colonizer and naïf traveller – and the native, that appears to be more ambiguous than it seemed at first sight. The Imperial legacy produces a definite notion of exotic Paradise that is finally reversed in the colonizer’s Hell.